Analysis of The Factors Motivating Dairy Farmers in The Southern Slope of Merapi Volcano to Return to Their Endangered Settlement Post Eruption 2010 - Andarwati, S; Rijanta, R; Widiati, R; Opatpatanakit, Y (ANIMAL PRODUCTION, 2014)
Abstract: This study aimed to analyze the factors motivating dairy farmers in disaster-prone area (DPA) in the southern slopes of Merapi volcano to return to their endangered settlement, post 2010 eruption. The research samples, using census method, were dairy farmers in DPA III (Kaliadem hamlet) and DPA II (Gondang Wetan hamlet), both in Cangkringan district. Study site was a disaster-prone areas, directly affected  by Merapi eruption in 2010. Villages in the affected areas selected with consideration had the highest population of dairy cattles before the eruption of Merapi  2010 and was the closest village to the peak. Research conducted by the survey method. The results showed that the value of Hosmer and Lemeshow 0.909, so the model was declared fit to the data. Value Omnibus Tests of model coefficients 0.000, it was concluded that the independent variables were used together influence to the willingness of farmers to return to their endangered settlement,  post eruption 2010.   Nagelkerke R square value of 0.818, which means the ability of the independent variables were explained 81.8% the models.  Independent variables that  motivated the  desire of farmers to return to their endangered settlement  were: 1) dairy cattle ownership, 2) education, 3) culture and 4) information. Odds ratio value were respectively: 2.166 (dairy cattle ownership), 1.402 (education), 225.287 (culture) and 0.017 (information).  Cultural factors had the highest propensity value for motivating dairy farmers  to return to their endangered settlement post the eruption of 2010.Key words: motivate, endangered settlement, dairy farmers, southern slopes, Merapi volcano  Abstrak: Penelitian ini bertujuan menganalisis faktor-faktor yang mempengaruhi keinginan peternak sapi perah di daerah rawan bencana di lereng selatan Gunungapi Merapi untuk kembali ke dusun asal mereka sebelum erupsi  2010. Sampel atau materi penelitian adalah peternak sapi perah di KRB III (Dusun Kaliadem) dan KRB II (Dusun Gondang Wetan). Kedua dusun termasuk wilayah Kecamatan Cangkringan. Pengambilan responden dilakukan menggunakan metode sensus. Lokasi penelitian merupakan daerah rawan bencana, yang secara langsung terkena dampak dari erupsi Merapi 2010. Desa di daerah bencana dipilih dengan pertimbangan memiliki populasi sapi perah terbanyak pada saat sebelum letusan Merapi 2010 dan merupakan desa terdekat dengan puncak Merapi. Penelitian dilakukan dengan metode survei. Hasil penelitian menunjukkan bahwa nilai Hosmer dan Lemeshow 0,909 sehingga model dinyatakan fit dengan data. Nilai Omnibus Tests dari model coefficients 0,000, maka disimpulkan bahwa variabel bebas yang digunakan secara bersama-sama berpengaruh terhadap keinginan peternak untuk  kembali ke lokasi dusun semula sebelum erupsi 2010. Nilai Nagelkerke R2 0,818 yang artinya kemampuan variabel bebas menjelaskan model sebesar 81,8%. Variabel bebas yang berpengaruh terhadap keinginan peternak untuk kembali adalah: 1) kepemilikan sapi, 2) budaya, 3) informasi dan 4) pendidikan. Nilai  Odds Ratio berturut-turut sebesar 2,166 (kepemilikan sapi), 225,287 (budaya), 0,017 (informasi) dan 1,402 (pendidikan). Faktor budaya memiliki nilai kecenderungan yang tertinggi untuk mempengaruhi keinginan peternak untuk kembali ke dusun semula sebelum erupsi 2010.Kata kunci: keinginan kembali, peternak sapi perah, lereng selatan, gunungapi Merapi